2015
DOI: 10.1007/s11682-015-9490-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased interhemispheric resting-state functional connectivity after sleep deprivation: a resting-state fMRI study

Abstract: Several functional imaging studies have investigated the regional effects of sleep deprivation (SD) on impaired brain function; however, potential changes in the functional interactions between the cerebral hemispheres after SD are not well understood. In this study, we used a recently validated approach, voxel-mirrored homotopic connectivity (VMHC), to directly examine the changes in interhemispheric homotopic resting-state functional connectivity (RSFC) after SD. Resting-state functional MRI (fMRI) was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 26 publications
4
33
1
Order By: Relevance
“…[6] In the present study, we revealed increased VMHC in the bilateral thalamus/posterior insula (including anterior insula), fusiform, middle cingulate gyrus, inferior parietal lobe, and postcentral gyrus in healthy participants with sleep disturbance. According to increased VMHC induced by sleep deprivation [21] and reduced frontal–parietal activation after sleep deprivation, [6] our results might reflect compensatory adaptation for dysfunction of the cognitive network after sleep disturbance. Obviously, a more comprehensive task design is needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…[6] In the present study, we revealed increased VMHC in the bilateral thalamus/posterior insula (including anterior insula), fusiform, middle cingulate gyrus, inferior parietal lobe, and postcentral gyrus in healthy participants with sleep disturbance. According to increased VMHC induced by sleep deprivation [21] and reduced frontal–parietal activation after sleep deprivation, [6] our results might reflect compensatory adaptation for dysfunction of the cognitive network after sleep disturbance. Obviously, a more comprehensive task design is needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 91%
“…[29] Insomnia mechanisms modulating the arousal network has been suggested from the thalamus. [3032] Zhu et al [21] reveal a significant increase in VMHC in the thalamus in 28 healthy participants after a total night of sleep deprivation. Li et al [18] find reduced fractional anisotropy in the thalamus, as well as negative correlation between fractional anisotropy in the thalamus and disease duration, in primary insomnia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased activation within DMN regions suggested a decreased efficiency in segregation of the DMN from task. Increased activation was also found in the thalamus in our study, which is consistent with previous TSD imaging studies (Chee and Chuah, ; Zhu et al ., ). These studies suggested a compensatory role of the thalamus for increasing the arousal level to counteract elevated sleep pressure after TSD (Chee and Chuah, ).…”
Section: Discussionmentioning
confidence: 97%